DAMPAK TEKNOLOGI PENDIDIKAN TERHADAP PERANAN GURU DI MASA DEPAN - Gusmaneli gusmaneli (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
The aim of this paper is to describe the application of technology on education and its impact on the learning process and teachers’ role in the future. This is library research, where the result of analysis showed that the future education is oriented on the students’ involvement on each learning activities. The students are hoped to be active and autonomous ones in using learning facilities and sources in line with the development of technology. The application of technology brings positive effect on the role of teachers in the future, which is signed by the changes of teachers’ role in the teaching and learning process.